A responsabilidade civil das organizações produtoras de embalagens plásticas em contato com alimentos: o caso do Bisfenol A e dos Ftalatos - Köhler, Graziela de Oliveira (Universidade do Vale do Rio dos Sinos, 2016)
This thesis concerns the civil liability of food plastic packaging producers for potential health risks associated with plastic materials. Plastics products are made from polymeric materials, and in some cases, they need to go through processes in order to add chemicals, such as Bisphenol-A (BPA) and Phthalates. These chemicals are seen as harmful to human and animal health; however, there is scientific uncertainty as to the degree of such harmfulness. Safety risks associated with plastic packaging materials generate undeniable challenges to the civil liability Institute, as its outdated structure does not reflect the complexity that exists nowadays. The main purpose of this study is to investigate the problems and determine structural alternatives to address such risks. The method used in the research was the pragmatic-systemic one, given that it presents an instrument, which allows the observation of the hypercomplex society and its communication processes. The theme is presented under the scope of the consumer protection law, extending to consumers’ diffuse rights. Civil liability is directed to an evolutionary procedure that differs from the traditional reparatory function, thus assuming a role as a manager of the risks and a builder of the future. The results include an articulation of dogmatic mechanisms to assimilate the risks of using plastic packaging materials, which involve the adoption of a prospective responsibility through damage precaution, the possibility of imposing liability without damage, such as prohibitory injunctions, and yet, be charged for the omission of information on scientific uncertainty. Through these mechanisms, the research focuses on formats that can reach the plastic packaging production chain, and, also on argumentative supplements that can be used in the decision-making process of lawsuits.
Keywords: Sistemas autopoiéticos; Responsabilidade civil; Polímeros; Riscos; Precaução; Autopoietic systems; Civil liability; Polymers; Risks; Precaution; ACCNPQ::Ciências Sociais Aplicadas::Direito